2021
DOI: 10.3389/fonc.2021.653005
|View full text |Cite
|
Sign up to set email alerts
|

FSCN1 Promotes Radiation Resistance in Patients With PIK3CA Gene Alteration

Abstract: Radiotherapy is one of the standard treatments for cervical cancer and head and neck cancer. However, the clinical efficacy of this treatment is limited by radioresistance. The discovery of effective prognostic biomarkers and the identification of new therapeutic targets have helped to overcome the problem of radioresistance. In this study, we show that in the context of PIK3CA mutation or amplification, high expression of fascin actin-bundling protein 1 (FSCN1) (using the median as the cut-off value) is assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…International Publisher pathogenesis molecular mechanisms and new therapeutic targets are essential [8,9].…”
Section: Ivyspringmentioning
confidence: 99%
“…International Publisher pathogenesis molecular mechanisms and new therapeutic targets are essential [8,9].…”
Section: Ivyspringmentioning
confidence: 99%
“…The 13q12.3 amplification in C1 contained HMGB1, which could promote the development of MDSC and the metastasis of cancer cells ( Gorgulho et al, 2019 ; Ren et al, 2021 ). FSCN1 amplification at 7p22.1, Gab2 amplification at 11q14.1, and CD44 amplification at 11p13 were also associated with promoting tumor invasion ( Ke et al, 2007 ; Li et al, 2018 ; Rohani et al, 2019 ) and inducing tumor resistance to radiotherapy ( Li et al, 2021 ), suggesting that patients with C1 had high immune suppression, active EMT, and may not be suitable for radiation therapy. The 19q13.42 amplification of C2 contained NLRP3, which could upregulate the expression of PD-L1 to form immunosuppression ( Lu et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…High FSCN1 expression has been revealed to be associated with worse outcomes in HCC ( 48 ). Increasing evidence showed that FSCN1 is involved in cell proliferation, apoptosis, motility, chemotherapeutic resistance, tumor growth, and metastasis of several malignancies ( 49 , 50 ). PI3K/AKT pathway was revealed by several reports to be a critical downstream target of FSCN1 ( 51 , 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely to ADORA2A-AS1, high expression of FSCN1 was correlated with poor outcome of HCC patients (48). FSCN1 was documented to exert oncogenic roles in several malignancies, including HCC (49,50). For example, FSCN1 was reported to promote HCC cellular proliferation, migration, and invasion, inhibit HCC cellular apoptosis, and increase HCC cellular doxorubicin resistance (55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%